Polarizer, polarizing plate and optical display device including the same

By using a polyvinyl alcohol film with a specific heat-absorbing peak and a protective film with a high initial shrinkage starting temperature, the problem of bubble generation by the polarizer at high temperature and thermal shock is solved, and the good reliability and light leakage suppression effect of the polarizer and polarizer are achieved.

CN115104049BActive Publication Date: 2025-03-11HAOSHENG HENGXIN (WUXI) MATERIALS CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202180014939.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2020-02-17
Filing Date
2021-02-08
Publication Date
2025-03-11
Estimated Expiration
2041-02-08

AI Technical Summary

Technical Problem

Existing polarizers are prone to bubbles under high temperatures and thermal shock, resulting in reduced reliability and light leakage.

Method used

Polarizers are manufactured using polyvinyl alcohol films with endothermic peaks of 50°C to 60°C, and protective films with high initial shrinkage starting temperatures are stacked on their surfaces to improve the reliability of the polarizer and prevent air bubble generation.

Benefits of technology

Under high temperature and thermal shock, the polarizer and polarizer can effectively prevent bubble generation, maintain good reliability and suppress light leakage.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115104049B_ABST
    Figure CN115104049B_ABST
Patent Text Reader

Abstract

A polarizer is provided, comprising a polyvinyl alcohol film and having an endothermic peak of 50°C to 60°C when measured by differential scanning calorimetry at a heating rate of 10°C / min; a polarizing plate comprising a polarizer and a first protective film and a second protective film respectively laminated on one surface and another surface of the polarizer, and the polarizing plate having an initial shrinkage initiation temperature greater than 70°C and less than or equal to 90°C during thermomechanical analysis; and an optical display device including the above.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a polarizer, a polarizing plate, and an optical display device including the same. More specifically, the present invention relates to a polarizer and a polarizing plate, and an optical display device including the same, which can prevent bubbles from being generated or observed with the naked eye when placed at high temperature and / or under thermal shock after forming a hole, can show good reliability when placed at high temperature and / or under thermal shock, and can suppress light leakage. Background Art

[0002] The polarizing plate may include a polarizer and a protective layer stacked on at least one surface of the polarizer. The polarizing plate may be used in an optical display device and may inevitably be exposed to high temperature and / or thermal shock for a long time. As a main characteristic of the polarizing plate, polarization is achieved by the polarizer of the polarizing plate. The polarizer is manufactured by uniaxially stretching a polyvinyl alcohol based film (polyvinyl alcohol based film, a film based on polyvinyl alcohol, a polyvinyl alcohol-based film) dyed with iodine. However, when placed under high temperature and / or thermal shock for a long time, the polarizing plate may suffer from degradation of reliability.

[0003] Polarizers can be manufactured by stretching polyvinyl alcohol films. Generally, polarizers are manufactured by dyeing and stretching polyvinyl alcohol films. Since typical polyvinyl alcohol films known in the art have limitations in stretching ratio and stretching temperature, polarizers produced therefrom have limitations in reliability improvement when placed at high temperatures and / or under thermal shock. When stretched at high stretch ratios and high temperatures, the polyvinyl alcohol film may break or melt during the stretching process, making it difficult to form a polarizer.

[0004] The polarizing plate may form a portion of a non-display area in which a camera is mounted in an optical display. In order to ensure a light transmission area for camera operation, a hole is formed on a portion of the polarizing plate, in particular, on a portion of the polarizer, by a chemical method or an optical method (laser irradiation, etc.). The hole may be implemented in the form of an opening formed through a portion of the polarizer, or may be formed to have a higher transmittance than a portion of the polarizer in which the hole is not formed, rather than being formed through the polarizer, such as an opening. However, even when placed at high temperatures and / or under thermal shock, the polarizing plate may suffer from the generation of bubbles around the hole, so that the bubbles can be observed by the naked eye, or a non-polarized portion may be formed due to the difference in refractive index caused by the bubbles, thereby causing display failure due to light leakage or poor image quality in the display area.

[0005] The background art of the present invention is disclosed in Korean Patent Publication No. 10-2013-0078606 and the like. Summary of the invention

[0006] Technical issues

[0007] One aspect of the present invention provides a polarizer and a polarizing plate, which can prevent the generation of bubbles or the observation of bubbles by the naked eye when placed under high temperature and / or thermal shock after forming holes, can show good reliability when placed under high temperature and / or thermal shock, and can suppress light leakage.

[0008] Another aspect of the present invention is to provide a polarizer and a polarizing plate prepared by a simple and economical method, which can prevent the generation of bubbles or the observation of bubbles by the naked eye when placed under high temperature and / or thermal shock after forming holes, can exhibit good reliability when placed under high temperature and / or thermal shock, and can inhibit light leakage.

[0009] Technical Solution

[0010] One aspect of the present invention relates to a polarizer.

[0011] 1. The polarizer includes a polyvinyl alcohol-based film and has an endothermic peak of 50° C. to 60° C. measured by differential scanning calorimetry at a temperature elevation rate of 10° C. / min.

[0012] 2. In 1, the polyvinyl alcohol-based film may contain both a hydrophilic functional group and a hydrophobic functional group.

[0013] 3. In 1-2, the polyvinyl alcohol-based film may have a softening point of about 65°C to about 71°C.

[0014] Another aspect of the present invention relates to a polarizing plate.

[0015] 4. The polarizing plate includes a polarizer and protective films stacked on one surface and the other surface of the polarizer, respectively, and has an initial shrinkage onset temperature of more than 70° C. and 90° C. or less measured by thermomechanical analysis at a heating rate of 10° C. / min.

[0016] 5. In 4, the polarizer may include a polyvinyl alcohol-based film and may have an endothermic peak of 50° C. to 60° C. measured by differential scanning calorimetry at a heating rate of 10° C. / min.

[0017] 6. In 4-5, the polyvinyl alcohol-based film may contain both a hydrophilic functional group and a hydrophobic functional group.

[0018] 7. In 4-6, the protective film may include a triacetylcellulose resin film, a polyethylene terephthalate resin film, or an amorphous cyclic polyolefin resin film.

[0019] 8. In 4-7, the protective film may have an initial shrinkage starting temperature of 70° C. to 130° C. measured by thermomechanical analysis at a heating rate of 10° C. / min.

[0020] Another aspect of the present invention relates to an optical display device.

[0021] An optical display device includes the polarizer or polarizing plate according to the present invention.

[0022] Beneficial Effects

[0023] The present invention provides a polarizer and a polarizing plate, which can prevent the generation of bubbles or the observation of bubbles with the naked eye when placed under high temperature and / or thermal shock after forming holes, can show good reliability when placed under high temperature and / or thermal shock, and can suppress light leakage.

[0024] The present invention provides a polarizer and a polarizing plate prepared by a simple and economical method, which can prevent the generation of bubbles or the observation of bubbles by the naked eye when placed under high temperature and / or thermal shock after forming holes, can show good reliability under high temperature and / or thermal shock, and can suppress light leakage. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 is a graph illustrating an initial shrinkage starting temperature of a polarizing plate according to one embodiment of the present invention measured by thermomechanical analysis.

[0026] Figure 2 is a graph depicting endothermic peaks of the polarizers of Example 1 (dashed line) and Comparative Example 1 (solid line) measured by differential scanning calorimetry. DETAILED DESCRIPTION

[0027] Best Mode

[0028] Hereinafter, embodiments of the present invention will be described in detail with reference to the accompanying drawings to provide a thorough understanding of the present invention to those skilled in the art. It should be understood that the present invention can be embodied in various ways and is not limited to the following embodiments.

[0029] Herein, the "endothermic peak" of a polarizer in measurement by differential scanning calorimetry (DSC) refers to the initial endothermic peak of the polarizer, as measured with respect to 5 mg to 10 mg of a polarizer sample in a heat flow manner while increasing the temperature from -50°C to 200°C at a heating rate of 10°C / min under a nitrogen atmosphere. Figure 2 , the temperature at which the heat flow temporarily decreases in the process of increasing with increasing temperature is defined as the endothermic peak.

[0030] Herein, the “initial shrinkage starting temperature” of a polarizing plate in measurement by thermomechanical analysis (TMA) means the initial shrinkage starting temperature of the polarizing plate measured in a nitrogen atmosphere while increasing the temperature from -50°C to 200°C, under a load of 0.02N to 0.05N, at a heating rate of 10°C / min, for a polarizing plate sample having a size of 8mm x 5mm (MD of polarizer x TD of polarizer) in a stretching direction (e.g., MD of polarizer).

[0031] Figure 1 The initial shrinkage starting temperature of various embodiments of the polarizing plate according to the present invention in the thermomechanical analysis is shown. Depending on the heating rate, the size of the polarizing plate sample is maintained or increased as the temperature increases and begins to shrink at a certain temperature. Here, the inflection point corresponding to the temperature at which the sample begins to shrink is defined as the initial shrinkage starting temperature measured by thermomechanical (TMA) analysis. For the measurement of the initial shrinkage starting temperature, the polarizing plate sample may have a thickness of 50 μm to 170 μm.

[0032] Herein, in the measurement by TMA analysis, the “initial shrinkage starting temperature” of the protective film may be a value measured on a sample having a size of 8 mm×5 mm (MD of protective film×TD of protective film) in the same manner as in the measurement of the initial shrinkage starting temperature of the polarizing plate.

[0033] As used herein, to express a specific numerical range, “X to Y” means a value greater than or equal to X and less than or equal to Y (X≤ and ≤Y).

[0034] As used herein, the term "(meth)acryloyl" refers to acryloyl and / or methacryloyl.

[0035] The inventors completed the present invention based on the following confirmation: the following polarizer and polarizing plate can prevent the generation of bubbles or the observation of bubbles by the naked eye when placed at high temperature and / or under heat shock after hole formation, can show good reliability while suppressing light leakage when placed at high temperature and / or under heat shock, and can be manufactured by a simple and economical method to improve processability and economic feasibility.

[0036] Here, a polarizer according to one embodiment of the present invention will be described.

[0037] The polarizer has an endothermic peak of 50°C to 60°C as measured by differential scanning calorimetry at a heating rate of 10°C / min. In differential scanning calorimetry, the endothermic peak refers to the phase transition temperature caused by the thermal history received by the polarizer during stretching when the polarizer is heated in a measurement by differential scanning calorimetry. Within the range of the endothermic peak, the polarizer formed with holes can prevent the generation of bubbles or the bubbles around the holes from being observed by the naked eye when placed at high temperatures and / or under thermal shock. In addition, within the range of the endothermic peak, the polarizer can significantly prevent shrinkage at high temperatures and / or under thermal shock, thereby even when placed at high temperatures and / or under thermal shock, the polarizer or a polarizing plate including the same can significantly prevent changes in polarization or transmittance while suppressing light leakage. For example, the polarizer may have an endothermic peak of 51°C to 59°C.

[0038] The polarizer may have a thickness of about 5 μm to about 30 μm, specifically, about 5 μm to about 15 μm. Within this range, the polarizer may be applied to a polarizing plate and a reduction in thickness of the polarizing plate may be achieved.

[0039] The polarizer is manufactured from a polyvinyl alcohol-based film by the process described below.

[0040] The polyvinyl alcohol film contains a hydrophilic functional group and a hydrophobic functional group. In addition to the hydrophilic functional group including a hydroxyl group (OH group) present in the polyvinyl alcohol film, a hydrophobic functional group is also present in the polyvinyl alcohol film. The polyvinyl alcohol film containing a hydrophilic functional group and a hydrophobic functional group is manufactured by the method described below, thereby achieving the endothermic peak and the shrinkage starting temperature according to the present invention.

[0041] The hydrophobic functional group is present in at least one of the main chain and the side chain of the polyvinyl alcohol resin forming the polyvinyl alcohol film. Here, the "main chain" refers to the part forming the main skeleton of the polyvinyl alcohol resin and the "side chain" refers to the skeleton connected to the main chain. Preferably, the hydrophobic functional group is present in the main chain of the polyvinyl alcohol resin.

[0042] The polyvinyl alcohol resin containing both hydrophilic and hydrophobic functional groups can be prepared by polymerization of at least one vinyl ester monomer such as vinyl acetate, vinyl formate, vinyl propionate, vinyl butyrate, vinyl pivalate, isopropenyl acetate, etc. and a monomer providing a hydrophobic functional group. Preferably, the vinyl ester monomer may include vinyl acetate. The monomer providing a hydrophobic functional group may include a monomer providing a hydrocarbon repeating unit, including ethylene, propylene, etc.

[0043] The polyvinyl alcohol-based film may have a softening point of about 65° C. to about 71° C., for example, about 67° C. to about 69° C. Within this range, the polyvinyl alcohol-based film does not suffer from melting and breaking when stretched.

[0044] The polyvinyl alcohol film can have a tensile strength of about 80 MPa to about 120 MPa, preferably about 90 MPa to about 110 MPa, as measured in the machine direction of the film. Within this range, the polyvinyl alcohol film will not suffer from melting and breaking when stretched, can provide high polarization by effective alignment of the polyvinyl alcohol molecular chain, and can easily produce a polarizer according to the present invention. The tensile strength of the polyvinyl alcohol film can be measured at 25 ° C by a universal testing machine (UTM) according to ASTM D882.

[0045] The polyvinyl alcohol-based film may have a thickness of greater than about 0 μm and about 50 μm or less, for example, about 10 μm to about 50 μm. Within this range, the polyvinyl alcohol-based film does not suffer from melting and breaking when stretched.

[0046] The polarizer is manufactured by sequentially subjecting a polyvinyl alcohol film to dyeing, stretching, and cross-linking processes.

[0047] The dyeing method includes treating a polyvinyl alcohol-based film in a dyeing bath containing a dichroic material. During the dyeing process, the polyvinyl alcohol-based film is immersed in the dyeing bath containing the dichroic material. The dyeing bath containing the dichroic material includes an aqueous solution containing the dichroic material and boric acid. In the dyeing bath containing the dichroic material and the boron compound, the polyvinyl alcohol-based film does not break even when dyeing and stretching are performed under the following conditions.

[0048] The dichroic material may include at least one iodine compound selected from potassium iodide, hydrogen iodide, lithium iodide, sodium iodide, zinc iodide, aluminum iodide, lead iodide and copper iodide. The dichroic material may be present in the dye bath, preferably in the dye solution, in an amount of about 0.5 mol / ml to about 10 mol / ml, preferably about 0.5 mol / ml to about 5 mol / ml. Within this range, the polyvinyl alcohol-based film can be uniformly dyed therewith.

[0049] The boron compound can help prevent the polyvinyl alcohol film from melting and breaking during stretching of the polyvinyl alcohol film. The boron compound can help prevent the polyvinyl alcohol film from melting and breaking even when the polyvinyl alcohol film is stretched at a high temperature and a high stretch ratio in a stretching process after a dyeing process.

[0050] The boron compound may include boric acid and / or borax. The boron compound may be present in the dyeing bath, preferably in the dyeing solution, in an amount of about 0.1 wt % to about 5 wt %, preferably about 0.3 wt % to about 3 wt %. Within this range, the polyvinyl alcohol-based film does not undergo melting and breaking when stretched, and high reliability can be achieved.

[0051] Preferably, the dyeing solution has a temperature of about 20 to about 50° C., specifically about 25 to about 40° C. During the dyeing process, the polyvinyl alcohol film may be immersed in the dyeing bath for about 30 to about 120 seconds, specifically about 40 to about 80 seconds.

[0052] The stretching method includes stretching the dyed polyvinyl alcohol-based film to about 5.7 times or more, for example, about 5.7 times to about 7 times, preferably about 5.8 times to about 7 times its original length at a stretching temperature of about 58° C. or higher, for example, about 58° C. to about 65° C. When stretched at the above stretching ratio and stretching temperature, a typical polyvinyl alcohol-based film melts and / or breaks, and thus cannot be formed into a polarizer.

[0053] The stretching process can be achieved by wet stretching or dry stretching. Preferably, the stretching process includes wet stretching to allow the use of boron compounds in the stretching process. Wet stretching includes uniaxially stretching the polyvinyl alcohol-based film in a machine direction in an aqueous solution containing a boron compound.

[0054] The boron compound may include at least one of boric acid and borax, preferably boric acid. In the stretching bath, preferably in the stretching solution, the boron compound may be present in an amount of about 0.5 wt % to about 10 wt %, preferably about 1 wt % to about 5 wt %. Within this range, the polyvinyl alcohol-based film does not undergo melting and fracture during stretching, and high reliability can be achieved.

[0055] The cross-linking process is performed to ensure strong adsorption of the dichroic material to the polyvinyl alcohol-based film subjected to the stretching process. The cross-linking solution used in the cross-linking process contains a boron compound. The boron compound, while strengthening the adsorption of the dichroic material, also contributes to improved reliability even when the polarizer is placed at high temperature or under thermal shock.

[0056] The boron compound may include at least one of boric acid and borax. The boron compound may be present in the crosslinking bath, preferably the crosslinking solution, in an amount of about 0.5 wt % to about 10 wt %, preferably about 1 wt % to about 5 wt %. Within this range, the polyvinyl alcohol film does not undergo melting and breaking when stretched, and high reliability can be achieved.

[0057] Prior to the dyeing process, the polyvinyl alcohol-based film may be further subjected to at least one of a washing process and a swelling process.

[0058] In the washing process, the polyvinyl alcohol-based film is washed with water to remove impurities from the polyvinyl alcohol-based film.

[0059] During the swelling process, the polyvinyl alcohol film is immersed in a swelling bath within a predetermined temperature range to promote dyeing and stretching of the dichroic material. The swelling method may include swelling the polyvinyl alcohol film at about 15°C to about 35°C, preferably about 20°C to about 30°C, for about 30 seconds to about 50 seconds.

[0060] After the cross-linking process, the polyvinyl alcohol-based film may be further subjected to a color correction process. The color correction process may improve the durability of the polyvinyl alcohol-based film. The color correction bath may optionally contain greater than about 0 wt % and up to about 10 wt %, preferably about 1 wt % to about 5 wt % potassium iodide.

[0061] In one embodiment, a portion of the polarizer may be formed with a hole, which forms a non-polarized area. When the polarizer is applied to an optical display device, the hole may constitute an area in which a camera is arranged. The hole may be formed by any method without limitation. For example, the hole may be formed by chemical treatment or optical treatment (such as laser irradiation). The hole may be realized in the form of an opening that penetrates a portion of the polarizer, or may be formed to have a higher transmittance than a portion of the polarizer that is not formed with a hole, rather than being formed through the polarizer.

[0062] After the hole is formed, when placed at high temperature and / or thermal shock, the polarizer may have bubbles formed at the interface of the hole, and the bubbles have a maximum size (diameter) of about 100 μm or less, for example, about 0 μm to about 100 μm. When the bubbles formed around the hole have a size of about 100 μm or less, in the display, the bubbles can be covered by the black matrix around the hole so that they will not be recognized by the user through the naked eye. In addition, even if several bubbles are connected to each other around the hole, if the maximum size of the bubbles from the center of the hole to the outside is about 100 μm or less, the bubbles cannot be recognized for the same reason.

[0063] Next, a polarizing plate according to one embodiment of the present invention will be described.

[0064] The polarizing plate includes a polarizer and a first protective film and a second protective film stacked on opposite surfaces of the polarizer, respectively, and has an initial shrinkage initiation temperature greater than 70°C and 90°C or less as determined by thermomechanical analysis. Within this range, the polarizing plate can exhibit good reliability when placed at high temperatures or under thermal shock. In addition, within this range, after the hole is formed, the polarizing plate can prevent the generation of bubbles or the observation of bubbles when placed at high temperatures and / or thermal shocks. For example, the polarizing plate can have an initial shrinkage initiation temperature greater than 70°C and 85°C or less, specifically, greater than 70°C and 80°C or less.

[0065] In one embodiment, the polarizing plate may have a polarization change ΔP1 of about 3% or less, for example, about 0% to about 3%, as calculated by Equation 1, and may have a polarization change of about 3% or less, for example, about 0% to about 3%, as calculated by Equation 2. Within this range, the polarizing plate has a low polarization change when placed at high temperature or under thermal shock, thereby ensuring good performance in terms of reliability, processability, and economic feasibility.

[0066] [Equation 1]

[0067] ΔP1=|P1-P0|

[0068] (In Equation 1, P0 is the initial polarization degree of the polarizing plate (unit: %), and

[0069] P1 is the polarization degree of the polarizing plate after being left at 95° C. for 500 hours (unit: %).

[0070] [Equation 2]

[0071] ΔP2=|P2-P0|

[0072] (In Equation 2, P0 is the initial polarization degree of the polarizing plate (unit: %), and

[0073] P2 is the degree of polarization of the polarizing plate after 100 cycles, each cycle being a process in which the polarizing plate is placed at -40°C for 30 minutes and at 80°C for 30 minutes (unit: %).

[0074] polarizer

[0075] The polarizer includes the polarizer according to the embodiment of the present invention.

[0076] The first protective film

[0077] The first protective film may be stacked on one surface of the polarizer to protect the polarizer while improving the mechanical strength of the polarizing plate. The first protective film may include an optically transparent protective film.

[0078] The protective film can be formed by melting and extruding an optically transparent resin. The protective film can be further stretched as needed. The resin may include a cellulose ester resin, including triacetyl cellulose, etc.; a cyclic polyolefin resin, including amorphous cyclic olefin polymer (COP), etc.; a polycarbonate resin; a polyester resin, including polyethylene terephthalate (PET), etc.; a polyether sulfone resin; a polysulfone resin; a polyamide resin; a polyimide resin; a non-cyclic polyolefin resin; a polyacrylate resin, including poly (methyl methacrylate), etc.; a polyvinyl alcohol resin; at least one of a polyvinyl chloride resin and a polyvinylidene chloride resin.

[0079] In one embodiment, the initial shrinkage initiation temperature of the first protective film may be 70° C. to 130° C., preferably 75° C. to 125° C., 80° C. to 120° C., 80° C. to 115° C., or 85° C. to 100° C., as measured by thermomechanical analysis at a heating rate of 10° C. / min. Within this range, when placed at high temperatures and under thermal shock, the first protective film can improve the reliability of the polarizing plate and the polarizer while suppressing the generation of bubbles around the holes.

[0080] The first protective film may have a thickness of about 5 μm to about 200 μm, specifically, about 20 μm to about 40 μm. Within this range, the first protective film may be used in the polarizing plate.

[0081] The polarizing plate may further include a functional coating layer on the upper surface of the first protective film, such as a hard coating layer, an anti-fingerprint layer, an anti-reflection layer, and the like.

[0082] Second protective film

[0083] The second protective film may be stacked on the other surface of the polarizer to protect the polarizer while improving the mechanical strength of the polarizing plate. The second protective film may be formed of the same resin as the first protective film or a different resin.

[0084] In one embodiment, when the first protective film is a cellulose ester resin film including triacetyl cellulose or the like, the second protective film may be a cellulose ester resin film including triacetyl cellulose or the like.

[0085] In another embodiment, when the first protective film is a polyester resin film including polyethylene terephthalate (PET) or the like, the second protective film may be a cyclic polyolefin resin film including amorphous cyclic olefin polymer (COP) or the like or a cellulose ester resin film including triacetyl cellulose or the like.

[0086] The second protective film may have the same thickness as the first protective film or a different thickness.

[0087] In one embodiment, the initial shrinkage initiation temperature of the second protective film may be 70°C to 130°C, preferably 75°C to 125°C, 80°C to 120°C, 80°C to 115°C or 85°C to 100°C, as measured by thermomechanical analysis at a heating rate of 10°C / min. Within this range, when placed at high temperatures and under thermal shock, the second protective film can improve the reliability of the polarizing plate and the polarizer while suppressing the generation of bubbles around the holes.

[0088] In the polarizing plate, the first protective film may be bonded to the second protective film via a bonding layer. The bonding layer may be formed by a bonding agent for a typical polarizing plate well known to those skilled in the art. For example, the bonding layer may be formed by a water-based bonding agent or a light-curing bonding agent. Preferably, the bonding layer is formed by a light-curing bonding agent to improve processability by increasing the chemical crosslinking rate of the organic acid anions in the zinc organic acid salt without the need for additional UV treatment for chemical crosslinking of the organic acid anions.

[0089] The photocurable adhesive may include an initiator and at least one selected from an epoxy compound and a (meth) acrylic compound. The initiator may include a photo radical initiator and / or a photo cationic initiator. The photocurable adhesive may further include typical additives such as antioxidants, pigments, etc. The adhesive layer may have a thickness of about 0.1 μm to about 10 μm. Within this range, the adhesive layer may be used in an optical display device.

[0090] The polarizing plate may further include an adhesive layer on a lower surface thereof to achieve adhesion of the polarizing plate to the liquid crystal panel. The adhesive layer may be formed of a pressure-sensitive adhesive, but is not limited thereto.

[0091] Next, an optical display device according to one embodiment of the present invention will be described.

[0092] The optical display device according to the present invention may include a polarizer or polarizing plate according to the present invention. The optical display device may include a liquid crystal display and / or a light-emitting display. The light-emitting display may include an organic or organic-inorganic light-emitting device as a light-emitting device, which may include a light-emitting diode (LED), an organic light-emitting diode (OLED), a quantum dot light-emitting diode (QLED), or a device containing a light-emitting substance such as a phosphor.

[0093] Invention Mode

[0094] Next, the present invention will be described in more detail with reference to some examples. However, it should be noted that these examples are provided for illustration only and should not be interpreted as limiting the present invention in any way.

[0095] Example 1

[0096] (1) Manufacturing of polarizer

[0097] A polyvinyl alcohol film (TS-#3000, Kuraray Co., Ltd., Japan, a film having a main chain containing a hydrophobic functional group, thickness: 30 μm, tensile strength (at 25° C.): 98 MPa) washed with 25° C. water was subjected to swelling treatment in a 30° C. water swelling bath.

[0098] Thereafter, the polyvinyl alcohol film was placed in a dyeing bath filled with an aqueous solution containing 1 mol / ml potassium iodide and 1 wt% boric acid for 65 seconds at 30° C. Next, the polyvinyl alcohol film was stretched to 5.9 times its original length in a wet stretching bath filled with an aqueous solution containing 3 wt% boric acid at 60° C. Next, the polyvinyl alcohol film was passed through a cross-linking bath filled with an aqueous solution containing 3 wt% boric acid at 25° C. for 65 seconds.

[0099] Next, the polyvinyl alcohol film was immersed in a color correction bath filled with an aqueous solution containing 4.5 wt % of potassium iodide at 30° C. for 10 seconds. Thereafter, the film was washed and dried, thereby manufacturing a polarizer (thickness: 12 μm).

[0100] (2) Manufacturing of polarizing plates

[0101] A polarizing plate is manufactured by applying a water-based adhesive to both surfaces of the manufactured polarizer, bonding a triacetyl cellulose (TAC) film (thickness: 30 μm, FujiTAC, Fuiji Co., Ltd.) to one surface of the polarizer, and bonding a TAC film (thickness: 20 μm, FujiTAC, shrinkage starting temperature: 90°C, Fuiji Co., Ltd.) to the other surface of the polarizer.

[0102] Examples 2 to 5

[0103] A polarizer and a polarizing plate were manufactured in the same manner as in Example 1, except that the content of each component in the dyeing bath, stretching bath, and crosslinking bath was changed together with the stretching temperature, stretching rate, and kind of protective film as listed in Table 1.

[0104] Comparative Example 1

[0105] A polyvinyl alcohol film (PE-#3000, Kuraray Co., Ltd., Japan, a film having no main chain containing a hydrophobic functional group, thickness: 30 μm) washed with water at 25°C was subjected to a swelling process in a 30°C water swelling bath.

[0106] Thereafter, the polyvinyl alcohol film was placed in a dyeing bath filled with an aqueous solution containing 1 mol / ml potassium iodide and 1 wt% boric acid for 65 seconds at 30° C. Next, the polyvinyl alcohol film was stretched to 5.7 times its original length in a wet stretching bath filled with an aqueous solution containing 3 wt% boric acid at 53° C. Next, the polyvinyl alcohol film was passed through a cross-linking bath filled with an aqueous solution containing 3 wt% boric acid at 25° C. for 65 seconds.

[0107] Next, the polyvinyl alcohol film was immersed in a color correction bath filled with an aqueous solution containing 4.5 wt % of potassium iodide at 30° C. for 10 seconds. Thereafter, the film was washed and dried, thereby preparing a polarizer (thickness: 12 μm).

[0108] A polarizing plate was manufactured in the same manner as in Example 1 using the manufactured polarizer.

[0109] Comparative Example 2

[0110] A polarizing plate was manufactured in the same manner as in Example 1 using a polyvinyl alcohol film (PE-#3000, Kuraray Co., Ltd., Japan, a film having no main chain containing a hydrophobic functional group, thickness: 30 μm).

[0111] The following properties of the polarizers and polarizing plates manufactured in the examples and comparative examples were evaluated, and the results are shown in Tables 1 and Figure 2 middle.

[0112] (1) Endothermic peak (unit: °C): 5 mg to 10 mg of polarizer sample was prepared, and then the temperature was increased from -50 °C to 200 °C at a heating rate of 10 °C / min in a heat flow manner. The initial endothermic peak was measured using a differential scanning calorimeter (Discovery, TA Instruments) under a nitrogen atmosphere.

[0113] (2) Initial shrinkage starting temperature (unit: °C): The polarizing plate was cut into samples with a size of 8 mm x 5 mm (MD of polarizer x TD of polarizer), and then treated in the stretching direction of the polarizer while increasing the temperature from -50 °C to 200 °C at a heating rate of 10 °C / min under a load of 0.02 N in a nitrogen atmosphere in a thermomechanical analyzer (Q400TMA, TA Instruments).

[0114] (3) Generation of hole bubbles: A polarizer was formed by stacking a glass substrate (0.5 T), a hole (circle with a radius of 5 mm) in each of the examples and comparative examples, OCA (optically clear adhesive, OCA-8371, 3M), and glass (0.5 T), and then irradiated with UVA at 2 J / cm 2UV curing is performed to manufacture the sample. The sample is subjected to 100 cycles, each cycle referring to a process in which the sample is placed at -40°C for 30 minutes and at 80°C for 30 minutes (under the same conditions of applying heat shock in (4)) to check the generation of bubbles around the holes. A polarizing plate having bubbles formed around the holes and having a maximum diameter of 100 μm or less is rated "X", and a polarizing plate having bubbles formed around the holes and having a maximum diameter greater than 100 μm is rated "○". If the bubbles formed around the holes have a maximum diameter of 100 μm or less, the bubbles can be covered by the black matrix around the holes in the display and will not be recognized by the user with the naked eye. However, if several bubbles are connected to each other around the holes to have a maximum size of 100 μm or less, as measured from the center of the hole to the outside, the user cannot recognize the bubbles for the same reason. Therefore, the corresponding polarizing plate is rated "X".

[0115] (3) Polarization change (unit: %): The polarizing plate was cut into a sample with a size of 3 cm x 7 cm (MD of polarizer x TD of polarizer), and then the polarizing plate was left at 95° C. for 500 hours and then the polarization degree at a wavelength of 380 nm to 780 nm was measured using V-7100 (JASCO). The polarization change was calculated according to Equation 1.

[0116] Regarding the change in polarization degree under heat shock, the polarization degree was measured at a wavelength of 380 nm to 780 nm using V-7100 (JASCO) before or after repeating 100 cycles, each cycle referring to a process in which the polarizing plate was placed at -40°C for 30 minutes and at 80°C for 30 minutes. Thereafter, the polarization change was calculated according to Equation 2.

[0117] [Table 1]

[0118]

[0119] In Table 1,

[0120] *Comparative Example 2: Since the polyvinyl alcohol film melted and broke during stretching, a polarizer could not be produced.

[0121] **COP:ZEON,ZB12-052125

[0122] As shown in Table 1 and Figure 2As shown, the polarizer according to the present invention has an endothermic peak of 50°C to 60°C as measured by differential scanning calorimetry, and the polarizing plate according to the present invention has an initial shrinkage initiation temperature of greater than 70°C and 90°C or less as measured by thermomechanical analysis at a heating rate of 10°C / min, thereby suppressing the generation of bubbles while ensuring reliability when placed under high temperature and thermal shock. In addition, although not shown in Table 1, the polarizer and polarizing plate according to the present invention exhibit good light leakage suppression when applied to an optical display device. In addition, although not shown in Table 1, the polarizing plate according to the present invention has an initial shrinkage initiation temperature of greater than 70°C and 90°C or less as measured by thermomechanical analysis, thereby suppressing the generation of bubbles around the holes.

[0123] On the contrary, as shown in Table 1 and Figure 2 As shown, the polarizer of Comparative Example 1 prepared using a typical polyvinyl alcohol film without a hydrophobic functional group has an endothermic peak of less than 50°C as measured by differential scanning calorimetry, and the polarizing plate of Comparative Example 1 has an initial shrinkage initiation temperature of 70°C or lower as measured by thermomechanical analysis at a heating rate of 10°C / min, thereby exhibiting poor reliability at high temperatures and under thermal shock, while allowing bubbles to be severely generated around the holes.

[0124] The polarizer of Comparative Example 2 could not be manufactured due to melting and breaking of the polyvinyl alcohol film having no hydrophobic functional group during stretching.

[0125] It should be understood that various modifications, changes, variations and equivalent embodiments may be made by those skilled in the art without departing from the spirit and scope of the present invention.

Claims

1. A polarizer comprising a polyvinyl alcohol-based film and having an endothermic peak of 50°C to 60°C measured by differential scanning calorimetry at a heating rate of 10°C / min, The polyvinyl alcohol-based film is formed of a polyvinyl alcohol-based resin, the polyvinyl alcohol-based resin contains both a hydrophilic functional group and a hydrophobic functional group, and the hydrophobic functional group is present in the main chain of the polyvinyl alcohol-based resin, in, The polyvinyl alcohol-based film has a softening point of 65°C to 71°C.

2. A polarizing plate comprising a polarizer and protective films respectively stacked on opposite surfaces of the polarizer, The polarizing plate has an initial shrinkage starting temperature greater than 70°C and less than or equal to 90°C measured by thermomechanical analysis at a heating rate of 10°C / min, The polarizer includes a polyvinyl alcohol-based film, the polyvinyl alcohol-based film is formed of a polyvinyl alcohol-based resin, the polyvinyl alcohol-based resin includes both a hydrophilic functional group and a hydrophobic functional group, and the hydrophobic functional group exists in the main chain of the polyvinyl alcohol-based resin, in, The polyvinyl alcohol-based film has a softening point of 65°C to 71°C.

3. The polarizing plate according to claim 2, wherein: The polarizer includes a polyvinyl alcohol-based film and has an endothermic peak of 50° C. to 60° C. measured by differential scanning calorimetry at a heating rate of 10° C. / min.

4. The polarizing plate according to claim 2, wherein: The protective film includes a triacetyl cellulose resin film, a polyethylene terephthalate resin film, or an amorphous cyclic polyolefin resin film.

5. The polarizing plate according to claim 2, wherein: The protective film has an initial shrinkage starting temperature of 70°C to 130°C measured by thermomechanical analysis at a heating rate of 10°C / min. 6 . An optical display device, comprising the polarizer according to claim 1 or the polarizing plate according to any one of claims 2 to 5.

Citation Information

Patent Citations

  • Polarizer plate and optical display device comprising the same

    KR1020130078606A

  • Optical film with high adhesiveness and polarizing plate comprising the same

    CN108700693A

  • Optical compensating sheet having optically anisotropic layer made of discotic liquid-crystalline molecules and transparent substrate comprising polymer film

    CN1561456A

  • Preparing method for thin polarizer, thin polarizer and polarizing plate comprising the same

    KR1020150082874A

  • Polarizing lens, eyewear, and method for manufacturing polarizing lens

    US20160349538A1